Intramyocardial gene silencing by interfering RNA - Brea, María Soledad (2017)
RNAi is a widely used methodology for gene silencing. The action mechanism of siRNA molecules has been well studiedin recent years, and the technique has been optimized in terms of safety and effectiveness. Cardiovascular diseases have a high incidence in the current population, and despite of the extensive research, safe and efficient therapeutics have notyet been found, which is reflected by 17.1 million people who die each year for this cause. In this context, siRNAs arebeing considered a therapeutic tool to regulate the expression of genes involved in the generation of these pathologies.The efficacy of siRNAs entry to cardiomyocytes, the safety of the delivery process and the degree of silencing achievedare main aspects before consider it as a cardiovascular disease therapy. Presently, we will give a brief outline of thecurrent understanding of the RNAi mechanism and the delivery system to the heart. We describe the use of lentivirus fora functional silencing of cardiac proteins in the study of a pathophysiological process, the slow force response to cardiac stretch.